1992
DOI: 10.1007/bf00196905
|View full text |Cite
|
Sign up to set email alerts
|

Discharge patterns of cochlear ganglion neurons in the chicken

Abstract: Physiological recordings were made of the compound action potential from the round window and single neurons in the cochlear ganglion of normal adult chickens (Gallus domesticus). The compound action potential threshold to tone bursts decreased from approximately 42 dB at 0.25 kHz to 30 dB between 1 and 2 kHz and then increased to 51 dB at 4 kHz. Most of the cochlear ganglion cells had characteristic frequencies below 2 kHz and the thresholds of most neurons were roughly 30-35 dB lower than the compound action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
41
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 34 publications
12
41
1
Order By: Relevance
“…The low CF NM neurons that we discuss here probably have a CF lower than 0.5 kHz, and this region of CF may not have been fully investigated in the barn owl. The vector strength of NM firing was reported as being ϳ0.8 at 0.4 kHz CF region in the chicken (Warchol and Dallos, 1990), and this is the same level of synchronization as that found in the ANFs at these CFs (Salvi et al, 1992). Both in the chicken and in the barn owl, additional examinations will be necessary regarding the temporal jitter and the possible improvement of temporal coding of neurons in the low CF region of NM by in vivo experiments.…”
mentioning
confidence: 62%
“…The low CF NM neurons that we discuss here probably have a CF lower than 0.5 kHz, and this region of CF may not have been fully investigated in the barn owl. The vector strength of NM firing was reported as being ϳ0.8 at 0.4 kHz CF region in the chicken (Warchol and Dallos, 1990), and this is the same level of synchronization as that found in the ANFs at these CFs (Salvi et al, 1992). Both in the chicken and in the barn owl, additional examinations will be necessary regarding the temporal jitter and the possible improvement of temporal coding of neurons in the low CF region of NM by in vivo experiments.…”
mentioning
confidence: 62%
“…In this respect, the barn owl exceeds all other species investigated by an octave or more (Sachs et al, 1974(Sachs et al, , 1980Johnson, 1980;Sullivan and Konishi, 1984;Kettner et al, 1985;Palmer and Russell, 1986;Hillery and Narins, 1987;Gleich and Narins, 1988;Rose and Weiss, 1988;Hill et al, 1989;Carr and Konishi, 1990;Manley et al, 1990Manley et al, , 1997Salvi et al, 1992;Joris et al, 1994). Although Teich et al (1993) claimed phase locking up to 18 kHz in auditory nerve fibers of the cat, this does not change the general conclusion of superior phase locking in the owl.…”
Section: Phase Locking Up To 10 Khz: How Is It Achieved?mentioning
confidence: 76%
“…This required some effort especially for the highest CFs Ͼ4,000 Hz. This added procedural difficulty presumably arose from the fact that there is a natural barrier, noted by others (Manley 1990;Manley et al 1985Manley et al , 1991Salvi et al 1992), that reduces access to the extreme basal regions of the ganglion. Adjustments in the electrode path were effective in mitigating this problem.…”
Section: Ontogeny Of Responses To Footplate Stimulationmentioning
confidence: 99%
“…Studies in embryos to date have reported the absence of primary afferent CFs տ2,200 Hz (primary afferents: Jones and Jones 1995a,b;central relays: Lippe andRubel 1983, 1985). The absence of primary afferent neurons with high-frequency CFs in late embryos has been hypothetically attributed to a functionally immature base, reduced transfer of high-frequency sound to the cochlea, and/or technical difficulties that prevent the assessment of the cochlear base (e.g., Jones and Jones 1995b;Manley 1990;Manley et al 1985Manley et al , 1991Salvi et al 1992). The research reported here was undertaken to critically examine these hypotheses.…”
Section: Introductionmentioning
confidence: 99%